Development of video-based learning media for christian religious education culture using the ADDIE model - Martha Anthoneta Talakua (12 Waiheru, 2023)
Development of video-based cultural learning media in Christian religious education subjects to build a harmonious life order for the Maluku people with various differences as learning material for students at school. So that children can know, understand, interpret and practice the behaviour of coexisting harmoniously in Maluku society. The purpose of this article is to help students understand multicultural material by using active, innovative, creative, effective and fun video-based cultural learning media in the teaching process. The video-based learning media development model is the ADDIE model which consists of 5 (five) stages, namely analysis, planning, development, implementation and evaluation. Learning media is made in video form with PowerPoint. It is hoped that it can help students in the class to better understand multicultural topics.